Evaluation of histopathological alterations in the gills of Vardar chub ( Squalius vardarensis Karaman) as an indicator of river pollution - Barišić, Josip; Dragun, Zrinka; Ramani, Sheriban; Filipović Marijić, Vlatka; Krasnići, Nesrete; Čož-Rakovac, Rozelindra; Kostov, Vasil; Rebok, Katerina; Jordanova, Maja (Elsevier BV, 2015)
Quanti!cation of histopathological alterations in the gills of Vardar chub (Squalius vardarensis Karaman) was performed in 2012 in rivers of north-eastern Macedonia, with the aim to examine the effects of water quality in the rivers (Zletovska and Kriva River-impacted by active Pb/Zn mines; Bregalnica River- contaminated by agricultural waste). The biological alterations in chub were classi!ed as: circulatory disturbances, regressive and progressive changes, but their severity differed. Altogether the mildest changes were observed in the gills of chub from the Bregalnica River, a less polluted river, whereas mining impacted rivers were characterized by more severe alterations. In the gills of chub from the Zletovska River, which is highly contaminated with numerous metals, sulphates and chlorides, the highest lesion indices were found for the regressive changes of both epithelium and supporting tissue, with typical lesions referring to atrophy, thinning and lifting of epithelial cells, necrosis of epithelium and chloride cells, as well as deformations of lamellar cartilaginous base. Gill damages of chub from the Kriva River were overall milder compared to the Zletovska River, in accordance with pollution status. In the gills of chub from that river, progressive changes were more pronounced, speci!cally severe hyperplasia of mucous cells and epithelium in the interlammellar space, leading to fusion of lamellae, as well as hypertrophy of chloride cells. The comparison between seasons indicated higher intensity of progressive changes in all three rivers in autumn, when water level was very low, and consequently, water con- tamination was more pronounced due to concentration effect. The pattern and severity of histopatho- logical alterations in the chub gills re"ected differences in contamination levels and type of contaminants in different rivers and sampling periods, and thus have been proven as a valuable indicator of water quality